2015
DOI: 10.1016/j.addr.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-mediated regulation of differentiation and trans-differentiation in stem cells

Abstract: MicroRNAs (miRNAs) are key components of a broadly conserved post-transcriptional mechanism that controls gene expression by targeting mRNAs. miRNAs regulate diverse biological processes, including the growth and differentiation of stem cells as well as the regulation of both endogenous tissue repair that has critical implications in the development of regenerative medicine approaches. In this review, we first describe key features of miRNA biogenesis and their role in regulating self-renewal, and then discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 171 publications
(183 reference statements)
0
38
0
2
Order By: Relevance
“…MicroRNAs are small (20–26 nucleotides in length) noncoding RNAs, which have been shown to exist widely in plants and animals (Valencia‐Sanchez, Liu, Hannon, & Parker, ; John et al, ). MicroRNAs can participate in many important biological processes, including proliferation, migration, invasion, and angiogenesis (Ong, Lee, Kodo, & Wu, ; Ronald, ). To date, multiple studies have shown that miR‐210 can function as a tumor suppressor by inhibiting cell proliferation and promoting apoptosis, such as in ovarian cancer (Giannakakis et al, ) and in esophageal squamous cell carcinoma (Tsuchiya et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs are small (20–26 nucleotides in length) noncoding RNAs, which have been shown to exist widely in plants and animals (Valencia‐Sanchez, Liu, Hannon, & Parker, ; John et al, ). MicroRNAs can participate in many important biological processes, including proliferation, migration, invasion, and angiogenesis (Ong, Lee, Kodo, & Wu, ; Ronald, ). To date, multiple studies have shown that miR‐210 can function as a tumor suppressor by inhibiting cell proliferation and promoting apoptosis, such as in ovarian cancer (Giannakakis et al, ) and in esophageal squamous cell carcinoma (Tsuchiya et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are present in animals and plants and have been detected in several human fluids (16). They are critical in many biological processes, including the regulation of cell differentiation, proliferation, apoptosis, angiogenesis, and metabolism (17). Specific plasma-related miRNAs were identified in maternal plasma or serum in normal pregnancies, as well as in pathological pregnancy conditions, such as PE (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, a single miRNA does not absolutely determine cell fate specification, and emerging evidence suggests that specific miRNAs have the potential to be involved in the transition from one cell type to another [50,51].. Our results suggested that miR26a could trigger MSC differentiation toward ECs by targeting GSK-3β, and GSK-3β-p21 signaling regulated EC differentiation (Fig. 1).…”
Section: Discussionmentioning
confidence: 51%